Tren Penelitian Kekerasan Berbasis Gender dalam Kesehatan Maternal: Analisis Bibliometrik Global - Mulyaningsih, Erika Agung; Retno Dwi Andayani, Sestu; Grah Prihartanti, Niken; Zubaidah, Risna (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2025)
Gender-based violence (GBV) during pregnancy is a global health issue that significantly impacts maternal and child health. This study aims to map research trends on GBV in maternal health using bibliometric analysis.This study utilized data from Scopus and Web of Science, analyzed using Publish or Perish and VOSviewer. Network visualization and co-occurrence analysis were conducted to identify publication patterns, keyword trends, and research interconnections.Eight main clusters were identified, including obstetric violence, pregnancy coercion, reproductive health, HIV/AIDS, and the impact of the COVID-19 pandemic on GBV. Research publications have increased significantly since 2018, with a major surge during the pandemic. Countries such as the United States, the United Kingdom, India, and South Africa dominate research in this field, while WHO plays a crucial role in policy interventions.The findings confirm that GBV during pregnancy is not only a health issue but also a social and global policy concern. Effective medical interventions, protective policies for pregnant women, and further research are necessary to mitigate the negative impacts of GBV on maternal and child health.